Concurrent interaction of DCs with CD4(+) and CD8(+) T cells improves secondary CTL expansion: It takes three to tango. - Hoyer, Stefanie; Prommersberger, Sabrina; Pfeiffer, Isabell; Schuler-Thurner, Beatrice; Schuler, Gerold; Dörrie, Jan; Schaft, Niels (European Journal of Immunology, 2014)
T-cell help is essential for CTL-memory formation. Nevertheless, it is unclear whether the continuous presence of CD4(+) T-helper (Th) cells is required during dendritic cell (DC)/CD8(+) T-cell encounters, or whether a DC will remember the helper signal after the Th cell has departed. This question is relevant for the design of therapeutic cancer vaccines. Therefore, we investigated how human DCs need to interact with CD4(+) T cells to mediate efficient repetitive CTL expansion in vitro. We established an autologous antigen-specific in vitro system with monocyte-derived DCs, as these are primarily used for cancer vaccination. Contrary to common belief, a sequential interaction of licensed DCs with CD8(+) T cells barely improved CTL expansion. In sharp contrast, simultaneous encounter of Th cells and CTLs with the same DC during the first in vitro encounter is a prerequisite for optimal subsequent CTL expansion in our in vitro system. These data suggest that, in contrast to DC maturation, the activation of DCs by Th cells, which is necessary for optimal CTL stimulation, is transient. This knowledge has significant implications for the design of new and more effective DC-based vaccination strategies. Furthermore, our in vitro system could be a valuable tool for preclinical immunotherapeutical studies.
EVALuna2:19507

Triggering of NF-κB in cytokine-matured human DCs generates superior DCs for T-cell priming in cancer immunotherapy. - Pfeiffer, Isabell; Hoyer, Stefanie; Gerer, Kerstin; Voll, Reinhard E.; Knippertz, Ilka; Gueckel, Eva; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (European Journal of Immunology, 2014)
Understanding the signaling that governs the immunogenicity of human dendritic cells (DCs) is a prerequisite for improving DC-based therapeutic vaccination strategies, in which the ability of DCs to induce robust and lasting Ag-specific CTL responses is of critical importance. Cytokine-matured DCs are regularly used, but to induce memory-type CTLs, they require additional activation stimuli, such as CD4+ T-cell help or TLR activation. One common denominator of these stimuli is the activation of NF-?B. Here, we show that human monocyte-derived, cytokine cocktail-matured DCs transfected with constitutively active mutants of I?B kinases (caIKKs) by mRNA electroporation, further upregulated maturation markers, and secreted enhanced amounts of cytokines, including IL-12p70, which was produced for more than 48 h after transfection. Most importantly, cytotoxic T cells induced by caIKK-transfected DCs combined high CD27 expression, indicating a more memory-like phenotype, and a markedly enhanced secondary expandability with a high lytic capacity. In contrast, CTLs primed and expanded with unmodified cytokine cocktail-matured DCs did not maintain their proliferative capacity upon repetitive stimulations. We hypothesize that "designer" DCs expressing constitutively active I?B kinases will prove highly immunogenic also in vivo and possibly emerge as a new strategy to improve the clinical efficacy of therapeutic vaccinations against cancer and other chronic diseases.
EVALuna2:19501